The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000473881
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Gastric Cancer: From Pure Morphology to Molecular Classifications

Abstract: Gastric cancer (GC) represents a global health concern. Despite advances in prevention, diagnosis, and therapy, GC is still the third leading cause of cancer mortality worldwide, with more than 720,000 estimated deaths in 2012. Overall survival for advanced disease is about 1 year, a dismal prognosis that is partly due to the high levels of biological heterogeneity found in GC. Indeed, GC is a highly heterogeneous disease from morphological and molecular standpoints. The numerous histological and molecular cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
119
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 107 publications
(149 reference statements)
4
119
0
4
Order By: Relevance
“…Although GC incidence and mortality has decreased throughout the years and novel therapies have been developed, less than one fifth of advanced GC patients survive 5 years post disease diagnosis [2,3]. Late diagnosis and high intra/inter-tumor heterogeneity likely explain this dismal prognosis and therapeutic failure [4]. Given the non-curative nature of gastric surgery in patients with advanced cancer, two targeted therapies have been approved to treat these patients: the monoclonal antibodies Trastuzumab (anti-HER2) and Ramucirumab (anti-VEGFR2) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Although GC incidence and mortality has decreased throughout the years and novel therapies have been developed, less than one fifth of advanced GC patients survive 5 years post disease diagnosis [2,3]. Late diagnosis and high intra/inter-tumor heterogeneity likely explain this dismal prognosis and therapeutic failure [4]. Given the non-curative nature of gastric surgery in patients with advanced cancer, two targeted therapies have been approved to treat these patients: the monoclonal antibodies Trastuzumab (anti-HER2) and Ramucirumab (anti-VEGFR2) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…STAD is a highly heterogeneous cancer, and tumor heterogeneity is instrumental in immune evasion [24][25][26][27][28] . In fact, several studies have shown that tumor infiltrating immune cells are prognostic markers for cancer progression [29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…Although surgery has improved the 5 year survival rate of patients with GC, the prognosis is still not optimistic. Gullo et al (15) showed that the prognosis of GC as a highly heterogeneous tumor is closely related to many factors. In addition to the traditional TNM staging system, it is also closely related to the body's immunity, inflammation, and nutrition.…”
Section: Discussionmentioning
confidence: 99%